Effects of Saffron Extract Supplementation on Mood, Well-Being, and Response to a Psychosocial Stressor in Healthy Adults: A Randomized, Double-Blind, Parallel Group, Clinical Trial - Jackson, Philippa A.; Forster, Joanne; Khan, Julie; Pouchieu, Camille; Dubreuil, Séverine; Gaudout, David; Moras, Benjamin; Pourtau, Line; Joffre, Florent; Vaysse, Carole; Bertrand, Karène; Abrous, Hélène; et al. (Frontiers in Nutrition, 2021)
Anxiety, stress, and low mood are closely related and may contribute to depressive symptoms. Among non-pharmacological solutions to improve sub-clinical mood symptoms and resilience to stress, natural products such as saffron—identified as promising following preliminary beneficial effects in major depressive disorder—represent a relevant strategy. The study assessed the efficacy of 8 weeks’ supplementation with 30 mg standardised saffron extract on emotional well-being in healthy adults with sub-clinical feelings of low mood and anxiety and/or stress, and evaluation of the acute effect of saffron in response to a lab based psychosocial stressor. The study adopted a double-blind, randomised, parallel groups design in which 56 healthy males and females (18 to 54 years) received either saffron extract or placebo for 8 weeks. Chronic effects of saffron on subjective anxiety, stress and depressive feelings were assessed using a questionnaire battery [including Profile of Mood State-2, (POMS)] and acute effects in response to a lab-based psychosocial stressor were measured through psychological and physiological parameters. Urinary crocetin levels were quantified. Participants who received the saffron extract reported reduced depression scores and improved social relationships at the end of the study. Urinary crocetin levels increased significantly with saffron supplementation and were correlated with change in depression scores. The typical stress-induced decrease in heart rate variability (HRV) during exposure to the stressor was attenuated following acute saffron intake. Saffron extract appears to improve subclinical depressive symptoms in healthy individuals and may contribute to increased resilience against the development of stress-related psychiatric disorders.